Proverbs in Aravind Adiga’s Novel: The White Tige - Salve, Prof. Sonba (American Journal of Literature Studies, 2024)
Proverbs are short and complex linguistic tools used in conversations as well as texts. Their brevity and power of expression is utilized by speakers and writes to say much with fewer words. Proverbs are used in literature such as dramas and novels. Writers use them to enhance meaning in their stories and create perspectives to make the unbelievable become believable. The perceived inherent general truth and element of universality of wisdom in proverbs is the reason as to why it is an important tool of writers who strive to convince their readers. Aravind Adiga has used proverbs in his novel, The White Tiger to that effect. This article is an investigation as to how the novelist has employed proverbs in the novel to create an enhanced sense of meaning. It explores the stylistical value they have added to his narration and the reason why the writer has depended on using proverbs in his work.